VALUE OF OBSERVANCE OF THE PROCEDURAL FORM OF INVESTIGATIVE ACTIONS IN CRIMINAL PROCEDURE - Sumbarova, Marina (Administrative and Criminal Justice, 2015)
In article author considered problems related to compliance of procedural form of investigative actions during criminal investigation. Research is connected with character of procedural form, proofs in criminal trial, analysis of theoretical and practical questions on a subject and opinions of scientists. The author connects observance of a form of investigative actions with quality of investigation of criminal trials, proofs, and their conceptual essence and defines problems of quality of investigation in aspect of implementation of the criminal procedure policy which is a component of criminal and legal policy of the state.